SURVEYING ANTIBIOTIC RESISTANCE OF STAPHYLOCOCCUS AUREUS CONTAMINATED IN CHILDREN AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe the current antibiotic resistance situation of S. aureus at Nghe AnObstetrics and Pediatrics Hospital.Subjects-methods: Cross-sectional description of specimens: blood, sputum, urine, bodyfluids, and pus from the patients diagnosed with infection who came for examination and treatmentat Nghe An Obstetrics and Pediatrics Hospital from January 2021 to January 2022.Results: S. aureus is strong resistant to many antibiotics, including benzylpenicillin (98.4%),clindamycin (81.5%), erythromycin (81.5%), tetracycline (77.2%). MRSA is also more resistant toother antibiotics than MSSA. The rate of resistance of MRSA to the benzylpenicillin, clindamycin,ciprofloxacin, erythromycin, oxacillin, rifampicin, tetracycline was higher than that of MSSA andthis difference was statistically significant (p
Keywords: Antibiotic resistance, Staphylococcus aureus, children.